Effect of heat treatment on microstructure and mechanical properties of Mg-4Y-1.6Nd-1Sm-0.5Zr alloy. (7th March 2018) - Jia, Guilong; Guo, Erjun; Feng, Yicheng; Wang, Liping; Wang, Changliang
Abstract: Microstructure and mechanical properties of Mg-4Y-1.6Nd-1Sm-0.5Zr alloy during heat treatments were investigated, while the room-temperature tensile fractographs were observed and analyzed. The results show that the eutectic phases almost dissolve into the matrix after being solutionized at 525 °C for 8 h. The ultimate tensile strength, yield strength and elongation reach 300 MPa, 219 MPa, 6.5% respectively after being under-aged at 200 °C for 16 h. The ultimate tensile strength and yield strength of the alloy decrease gradually, while the elongation increases gradually with increasing the test temperatures. The room-temperature tensile fracture modes of the as-cast alloy, solutionized alloy, aged alloy are mixed fracture of transgranular and intergranular, transgranular cleavage fracture, transgranular fracture, respectively.